A multiple regression analysis of six factors concerning school district demographics and superintendent tenure and experience in 2007-2008 schools relative to student achievement on the third grade Kansas reading assessments - Myers, Scott P. (Kansas State University, 2010)
The purpose of this quantitative study was to examine the relationship between the length of tenure of a superintendent and academic achievement as defined by the percentage of students who scored “Proficient” or better on the 2008 Third Grade Kansas Reading Assessment. To put this relationship into context, five other predictive variables were included as a part of this study: the individual’s total length of experience as a superintendent, the individual’s total length of experience in education, each district’s assessed valuation per pupil, each district’s percentage of students who qualified for free or reduced meal prices, and each district’s total student headcount. To gain the most comprehensive view possible, all 295 Kansas school districts in existence in 2008 were included in this study. The backward method of multiple regression was utilized to analyze these data. Before performing this analysis, the researcher first checked to ensure that the assumption of no multicollinearity had been met. From this analysis, all six predictive variables were retained as no relationships between them were found to be too strong. Following this check, the backward method of multiple regression analysis was performed. This method of multiple regression seeks to create the most parsimonious model, so two of the predictive variables were excluded from the final summary model based on removal criterion, the significance value of the t-test of each predictive variable. Results of this study revealed that 9.9% of the variance in the dependent variable, the percentage of students who scored “Proficient” or better on the 2008 Third Grade Kansas Reading Assessment, was accounted for by the predictive variables in the model retained. Further, multiple regression analysis tested the unique contributions of the four remaining predictive variables. Although included as one of the four predictive variables that had a significant effect on the percentage of students who scored “Proficient” or better on the 2008 Third Grade Kansas Reading Assessment, the primary focus of this study – to examine the impact a superintendent’s length of tenure has on students’ academic achievement – proved to have the least relative impact, according to beta weights.
Keywords: Multiple Regression; Length of Tenure of Superintendent; District Demographics; Education, Administration (0514)